Diagnostic accuracy of (18)F-FDG PET-CT in differentiating benign from malignant adrenal pathology. (1st March 2022) - Bosch, Karen; Parthipun, Arum; Harrington, Cuan; Khoo, Bernard; Banga, Neal
Abstract: Introduction: 18-fluorodeoxyglucose positron emission tomography-computed tomography ( 18 F-FDG PET-CT) is considered useful in the characterisation of adrenal masses. Herein, we evaluate the diagnostic accuracy of pre-operative 18 F-FDG PET-CT in patients undergoing adrenalectomy. Methods: Medical records of patients with 18 F-FDG PET-CT scans who subsequently underwent adrenalectomy in our centre were retrospectively analysed. Lesions were graded quantitatively using SUVmax and compared with histopathology results, which were classified as benign (Weiss score <3 for adrenocortical tumours, PASS <4 for phaeochromocytomas) or malignant. Results: Of 50 patients (median age 58 years) who had both 18 F-FDG PET-CT and histological results from adrenalectomy, 52% (26/50) had benign pathology on histopathological analysis (18 functional adenomas, 8 non-functional masses; median diameter 44mm [range 25–72mm]); 48% (24/50) had malignant lesions (9 adenocortical carcinoma, 6 metastases, 4 phaeochromocytomas with PASS >3, 2 adrenocortical tumours with Weiss >2, 3 other; median diameter 133mm [range 15–290mm]). Malignant lesions were significantly more avid on 18 F-FDG PET-CT than benign lesions (SUVmax 14.6±1.8 versus 5.3±0.7; p<0.001). Primary malignant adrenal tumours (Weiss score >2) were more avid than benign adenomas (Weiss score <3; SUVmax 15.3±1.7 versus 5.7±1.2; p<0.001). Indeed, Weiss Score correlated significantly with SUVmax on bivariate analysis (rs=0.87, p<0.001). Adrenal metastases were significantly more avid than benign adenomas (SUVmax 12.6±3.5 versus 5.7±1.2; p=0.04), but phaeochromocytomas were not (SUVmax 6.8±0.7; p=0.35). Conclusion: 18 F-FDG PET-CT lesion avidity can reliably distinguish between benign and malignant adrenal tumours, including metastases.